Study on Single and Combination of Galangal, Turmeric, and Ginger Ethanol Extracts as Anthelmintic - Azhari, Muhammad; Sengaji, Riki Febriansyah; Hadisoebroto, Ginayanti; Al-Badri, Faiq Muhamad Fathan (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Soil-Transmitted Helminth infection (STH) such as ascariasis, has become one of the most persistent parasitic diseases in most developing countries, including Indonesia. Galangal, turmeric, and ginger plants are known to provide various of pharmacologically active substances which commonly used as antibacterial, aphrodisiac, and antiparasitic. This research was aimed to study the anthelmintic activity of ethanol extract of ginger, turmeric, galangal in single extract as well as their combination against Ascaris suum Goeze as a model. The anthelmintic activity was analyzed by determining the profile of time of paralysis (TOP), time of death (TOD), and the IC50 of the inhibition activity from single extracts and extract combinations as well as the combination index (CI). The results showed that galangal, turmeric, and ginger ethanol extract have anthelmintic activity with IC50 7.66, 22, and 13,14 mg/mL, respectively. Meanwhile, the IC50 values for the extract combination of galangal with turmeric (KL), galangal with ginger (JL), and turmeric with ginger (JK) were 10.22; 3.92; and 34.93 mg/mL, respectively. The synergistic combination properties were shown by combination of galangal with turmeric extracts and galangal with ginger extracts with the combination index (CI) 0,67 and 0,38, respectively.